The association between CGRP gene -624 T?C polymorphism and headache severity in Turkish migraine patients - Etem, Ebru; Çetin, Sezgin; Koşan, Seda; Elyas, Halit; Müngen, Bülent (My University, 2024)
Aim: This study aims to explore -624 T?C polymorphism on CGRP gene in migraine patients, and the relation between this polymorphism and migraine attacks. Materials and Methods: The study registered a total of 101 migraine patients, 17 with aura and 84 without aura and 80 healthy volunteers. CGRP -624 T?C polymorphism in migraine patients and the control group was evaluated using PCR-RFLP method. Results: Although no significant difference could be found between genotype and allele frequencies of CGRP -624T?C polymorphism in the patient and control groups (p>0.05). In addition, a statistically significant positive correlation was established between the severity of headache and C allele of this gene in migraine patients (p<0.05). Conclusion: The fact that C allele of CGRP gene is at a higher rate in those with severe migraine attacks suggests that this allele can render neuroinflammation more marked by increasing the amount of CGRP. However, how CGRP -624T?C polymorphism influences the expressian level of the gene is not known for sure yet.
Keywords: Migraine; Gene polymorphism; CGRP